2006
DOI: 10.1177/096739110601400208
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Wood Flour with Maleic Anhydride for Manufacture of Wood-Polymer Composites

Abstract: Composites consisting of synthetic polymers and natural organic fillers have many applications. Plant-based materials, particularly wood, are used as fillers. Most frequently they are added to the polymer in the shape of wood flour or wood fibres. This type of polymer composite allows the possibility of modifying the components in accordance with the requirements of the application. Modifications to wood flour (WF) were carried out with a 10% solution of maleic anhydride (MA) in acetone in the presence of benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…One approach to reduce hygroscopicity is esterification of the wood component. Modification of wood with maleic anhydride improves its mechanical properties and induces stability while reducing water absorption [ 13 ]. The studies by Rahman et al [ 14 ] show that the incorporation of maleic anhydride increases the flexural strength and flexural modulus of composites compared to the ungrafted ones.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to reduce hygroscopicity is esterification of the wood component. Modification of wood with maleic anhydride improves its mechanical properties and induces stability while reducing water absorption [ 13 ]. The studies by Rahman et al [ 14 ] show that the incorporation of maleic anhydride increases the flexural strength and flexural modulus of composites compared to the ungrafted ones.…”
Section: Introductionmentioning
confidence: 99%
“…Maleic anhydride (MAH) and succinic anhydride also have been used to treat cellulosic materials (Roberts and Tatham 1992;Hubbe et al 1999;Nenkova et al 2006;Kamel et al 2008;Stenstad et al 2008). For instance, such an approach has been used to induce negative charges on the surfaces of microfibrillated cellulose (Kamel et al 2008;Stenstad et al 2008).…”
Section: Carboxylationmentioning
confidence: 99%
“…Though it is possible to carry out such reactions by heating cellulose fibers in the presence of dry MAH, it has been found that conditions may have to be controlled carefully to avoid undesired embrittlement of such fibers (Hubbe et al 1999). Researchers have demonstrated improved composite formation of MAH-treated cellulosic materials with polyolefins in certain cases Nenkova et al 2006;Kamel et al 2008). A related approach has involved addition of MAH as a separate component during compounding of composites that contain suitable matrix copolymers and cellulosic materials (Shi et al 2007).…”
Section: Carboxylationmentioning
confidence: 99%
“…There are many reports about the effects of chemical modification on solid wood and wood composites. Lignocellulosic fibers esterified with maleic anhydride and used to prepare composites present reduced moisture absorption of both fibers and the resulting composites in comparison to that of the untreated system .…”
Section: Introductionmentioning
confidence: 99%